THE ROLE OF FISHERY SUPERVISORS IN RESOLVING ILLEGAL AND DESTRUCTIVE FISHING CRIMES IN NORTH MALUKU, INDONESIA - Faisal Faisal; Robert Lengkong Weku; Dewi Suyatni; Nurlaila Kadarwati Papuluwa; Nur Aida Ikrima; Arief Budiono; Warda Said (RADJA PUBLIKA, 2025)
Indonesia’s Marine Fisheries Resources Supervisory Agency is a government institution under the Ministry of Maritime Affairs and Fisheries which is committed to continuing to combat illegal fishing and destructive fishing, considering that illegal fishing activities that often occur are fish theft by foreign fishing vessels originating from several neighboring countries. The aim of this research is to analyze the role of fishery supervisors in supervising illegal fishing and destructive fishing practices in North Maluku Province. This was empirical legal research which utilizes both literature review and fieldwork, including interviews. The research results demonstrate the urgency of criminal law's function as an ultimum remedium. To support the realization of sustainable development in the fisheries sector, it is necessary to regulate alternative sanctions for perpetrators of illegal and destructive fishing that are anticipatory in nature. These alternative sanctions can take the form of sanctions aimed at social and economic improvements and repair of damage to fish resources and their ecosystems caused by illegal and destructive fishing practices. Fishery supervisors have the role in supervising illegal and destructive fishing practices in North Maluku Province. The Fishery Supervisory law enforcement system and partners have the role in stopping illegal fishing practices and destructive fishing in North Maluku Province.